2003
DOI: 10.1096/fj.03-0040fje
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated functions of Akt/PKB and ETS1 in tubule formation

Abstract: We investigated the inter-relationship between two downstream effectors of vascular endothelial growth factor (VEGF), the serine-threonine kinase Akt (or protein kinase B) and the transcription factor ETS1, in tubulogenesis. We show that VEGF upregulates ETS1 transcription through an Aktdependent pathway in primary endothelial cells. Activation of Akt also results in tubule formation in vitro, a process requiring ETS1 activity. In vivo, the Drosophila ETS1 is required for cell motility per se while Akt is resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 37 publications
(49 reference statements)
3
25
0
Order By: Relevance
“…Ets can also mediate similar communication across different tumor and stroma compartments. VEGF, produced by tumor cells and fibroblasts, can induce Ets1 expression in endothelial cells [Lavenburg et al, 2003]. Concomitantly, Ets1, in cooperation with Hif-2a, activates the transcription of VEGF receptor 2 [Elvert et al, 2002].…”
Section: Epithelial-stromal Cell Interactions and The Tumor Micro-envmentioning
confidence: 99%
“…Ets can also mediate similar communication across different tumor and stroma compartments. VEGF, produced by tumor cells and fibroblasts, can induce Ets1 expression in endothelial cells [Lavenburg et al, 2003]. Concomitantly, Ets1, in cooperation with Hif-2a, activates the transcription of VEGF receptor 2 [Elvert et al, 2002].…”
Section: Epithelial-stromal Cell Interactions and The Tumor Micro-envmentioning
confidence: 99%
“…Activation of the Rho GTPases (Maru et al, 1998;Rogers et al, 2003;Wozniak et al, 2003), PI3-K (Lavenburg et al, 2003), and the MAPK family members (Khwaja et al, 1998;Ishibe et al, 2003Ishibe et al, , 2004O'Brien et al, 2004) has been shown to play a 3 ) were plated in collagen I/MG gels as described in Materials and Methods. In the top three panels, the gels were fixed 2, 4, and 6 d after plating, stained with rhodamine-phalloidin, and subjected to confocal microscopy as described in Materials and Methods.…”
Section: Branching In R-ras and Tc21 Ub Cells Is Mediated By Activatimentioning
confidence: 99%
“…However, activation of the Ets1 transcription factor has emerged as an important downstream regulator of angiogenic cell movement. Endothelial cell (EC) growth factors, such as vascular endothelial growth factor (VEGF) and fibroblast growth factor, specifically upregulate the activity of Ets1 in primary EC [2, 3] resulting in the activation of downstream target genes, such as metalloproteinases and vimentin [4] that are important for matrix degradation and cell migration [5]. In addition, antisense Ets1 can block the proangiogenic function of VEGF in cultured EC [2, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cell (EC) growth factors, such as vascular endothelial growth factor (VEGF) and fibroblast growth factor, specifically upregulate the activity of Ets1 in primary EC [2, 3] resulting in the activation of downstream target genes, such as metalloproteinases and vimentin [4] that are important for matrix degradation and cell migration [5]. In addition, antisense Ets1 can block the proangiogenic function of VEGF in cultured EC [2, 6, 7]. Thus, Ets1 appears to be a major regulator of migratory potential in response to chemotactic growth factors, a function that is also evolutionarily conserved [2, 8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation